Formation of subject specific competences of future teachers of computer science in practical classes on linear algebra - Армаш, Тетяна Сергіївна (Pedagogy of Higher and Secondary Education, 2015)
Armash T. S. Formation of subject specific competences of future teachers of computer science in practical classes on linear algebra. The tasks of different levels are considered: basic, high-level and creative for the subject of «Linear Algebra», which contribute to the formation and development of subject specific competences of future teachers of computer science on a practical training of linear algebra. Examples are given on specific topics. The content of the practical training on linear algebra for future teachers of computer science.